Therapeutic experience with hepatoblastoma associated with trisomy 18. Issue 8 (27th April 2018) - Inoue, Akiko; Suzuki, Ryo; Urabe, Keisuke; Kawamura, Yutaro; Masuda, Midori; Kishi, Kanta; Takitani, Kimitaka; Katayama, Hiroshi; Tomiyama, Hideki; Hayashi, Michihiro; Nemoto, Shintaro; Uchiyama, Kazuhisa; et al.
Abstract: Trisomy 18 is often fatal, but patients with this disease can now have longer survival due to proactive treatment intervention. However, hepatoblastomas may develop in these patients. In this study, we report four cases of hepatoblastoma associated with trisomy 18. All of the patients had congenital heart disease and three had undergone intracardiac surgical repair. Tumor growth was relatively slow in all cases, and there were no problems with chemotherapy tolerability and surgical resection. Three of the patients are currently disease‐free and the fourth is alive with remaining of the tumor. These cases suggest that combined chemotherapy and surgical resection may be an option to treat hepatoblastoma associated with trisomy 18 when cardiac pulmonary function is relatively stable.